Short Communication: Expression of APOBEC3G and Interferon Gamma in Pleural Fluid Mononuclear Cells from HIV/TB Dual Infected Subjects - Toossi, Zahra; Meng, Qinglai; Aung, Htin; Liu, Shigou; Mayanja-Kizza, Harriet; Hirsch, Christina S (AIDS research and human retroviruses, 2015)
Sites of HIV/TB coinfection are characterized by increased HIV-1 replication and a TH1 profile. However, expression of HIV-1 restriction factors, such as APOBEC3G (A3G) in situ, is unknown. Using an RT-profiler focused on genes related to HIV-1 expansion, we examined pleural fluid mononuclear cells (PFMCs) from patients with HIV/TB coinfection in comparison to HIV-uninfected patients with TB disease. Significant expression of interferon (IFN)-γ and restriction factors A3G and A3F and TRIM5α in PFMCs was found. Genes correlating significantly with the expression of IFN-γ included A3G and A3F. However, pleural fluid HIV-1 viral load and HIV-1 gag/pol mRNA in PFMCs did not correlate with A3G activity.